Fermi surface distortion induced by interaction between Rashba and Zeeman effects - Choi, Won Young; Chang, Joonyeon; Kim, Hyung-jun; Lee, Kyung-Jin; Koo, Hyun Cheol (AMER INST PHYSICS, 2015)
To evaluate Fermi surface distortion induced by interaction between Rashba and Zeeman effects, the channel resistance in an InAs quantum well layer is investigated with an in-plane magnetic field transverse to the current direction. In the magnetoresistance curve, the critical point occurs at similar to 3.5 T, which is approximately half of the independently measured Rashba field. To get an insight into the correlation between the critical point in magnetoresistance curve and the Rashba strength, the channel conductivity is calculated using a two-dimensional free-electron model with relaxation time approximation. The critical point obtained from the model calculation is in agreement with the experiment, suggesting that the observation of critical point can be an alternative method to experimentally determine the Rashba parameter. (C) 2015 AIP Publishing LLC.
Keywords: SPIN; DEPENDENCE